Sensorless control of SynRMs using an adaptive 2DoF current control including a comparison of two alternating HF signal injection-based methods - Bugsch, Martha; Held, Andreas; Piepenbreier, Bernhard (42nd Conference of the Industrial Electronics Society, IECON 2016, 2016)
Increasing interest in synchronous reluctance machines (SynRMs) shows the need to examine sensorless control methods for this machine type. For different speed ranges, different sensorless methods are necessary. The basic control structure used here is a cascaded field-oriented control (FOC) with a Two-Degree-of-Freedom (2DoF) current control with adaptive tracking controllers. This paper compares two alternating high-frequency (HF) test signal injection-based sensorless control methods for standstill and low speed. The first one superimposes an alternating HF test current signal and the second one an alternating HF test voltage signal onto the fundamental quantities in the estimated synchronous reference frame. To control the whole speed range, a method for the medium and upper speed range is necessary. Therefore, a back-EMF-based method is used. The implementation- and measurement-based differences for both alternating HF signal injection methods are analysed and the existing advantages and drawbacks are compared. Experimental results are included. They prove a similar behaviour of both alternating HF test signal-based sensorless control methods.
Keywords: HF test voltage injection; Sensorless control; Synchronous reluctance machines; 2DoF; Alternating test signal injection; HF test current injection